Net Carbohydrate Consumption is Associated with Cortical Thickness in Cognitively Impaired Older Adults with Confirmed Amyloid Burden. (20th December 2022) - Bramen, Jennifer E.; Popa, Emily S.; Rapozo, Molly K.; Siddarth, Prabha; Hodes, John F.; Ganapathi, Aarthi S.; Slyapich, Colby B.; Glatt, Ryan M.; Porter, Verna R.; Wong, Claudia L.; Bookheimer, Susan Y.; Roach, Jared C.; et al.
Abstract: Background: A low carbohydrate diet has been suggested as a treatment for Alzheimer's disease (AD) 1, 2 . One of the features of AD is widespread cortical thinning 3 ; however, no study has demonstrated that carbohydrate intake is linked to cortical thickness in patients with confirmed AD‐related neuropathology. The aim of this study is to test the hypothesis that higher carbohydrate intake is associated with thinner cortex. Method: Cortical thickness was estimated from T1‐weighted MR images using FreeSurfer with an alpha of p<0.05 (vertex‐wise) and p<0.01 (cluster‐wise correction for multiple comparisons). We calculated net carbohydrate intake using a Food Frequency Questionnaire (FFQ) as input to the validated FFQ EPIC Tool for Analysis 4 in 22 participants aged 57‐84 (mean = 70.1 years, SD = 6.2) with a diagnosis of mild cognitive impairment (MCI) or mild AD and confirmed amyloid burden. Results: Participants, on average, ate moderate to low levels of net carbohydrates (mean = 124 g, SD = 66). No participant exceeded the USDA guidelines for net average daily carbohydrate intake 5 . Most ate less than CDC guidelines for managing diabetes 6 (N = 19). Participants were drawn from the Pacific Brain Health Center, a clinical practice centered around addressing lifestyle and located in Santa Monica, California. We found that higher net carbohydrate intake was significantly associated with thinner cortex, accounting for age, within the left middle frontal gyrus (size = 2900 mm 2 ). Uncorrected results (cluster size>100 mm 2 ) showed that throughout the cortex, we saw a widespread pattern of cortical thinning, including regions within the middle temporal, fusiform, lingual, supramarginal, cingulate, superior parietal, postcentral, paracentral, orbitofrontal, inferior parietal, superior frontal gyri and insula. Only one region, the postcentral gyrus, showed a positive correlation, strongly suggesting the validity of these findings. Conclusions: Higher carbohydrate intake was significantly associated with thinner cortex in this cross‐section of older adults with cognitive impairment and confirmed amyloid burden. Prior research in older adults eating a Mediterranean diet did not detect this association 7 . Our sample was unique in that they ate fewer carbohydrates and had a diagnosis of cognitive decline with confirmed amyloid burden. Future directions of this research will assess how longitudinal trajectories of cortical thinning are impacted by changes in net carbohydrate consumption.